2010
DOI: 10.1520/jai102280
|View full text |Cite
|
Sign up to set email alerts
|

Using Directional Flame Thermometers for Measuring Thermal Exposure

Abstract: One of the recommendations that came from the NIST investigation of the World Trade Center disaster was the need for quantitative heat flux measurements in larger scale fire safety tests. These heat flux data are needed to support the development of engineering models to predict the performance of fire protection materials and systems. Current standardized fire resistance tests such as ASTM E119 or ISO 834 or IMO A754 are all qualitative tests. The furnace temperature is controlled to a standard time-temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Several alternative robust devices have been studied and developed to measure heat flux in fire conditions. [10][11][12][13] However, these alternative devices were not without fault, and it was identified that there were various issues such as inconsistencies in the heat flux estimates, slow response times, and various miscellaneous design flaws. [10][11][12][13] To resolve some of these adverse issues, Sullivan and McDonald 14 developed a robust and inexpensive custom-built sensor, capable of measuring high heat loads in wildland fire scenarios for extended periods of time, without the use of external cooling.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several alternative robust devices have been studied and developed to measure heat flux in fire conditions. [10][11][12][13] However, these alternative devices were not without fault, and it was identified that there were various issues such as inconsistencies in the heat flux estimates, slow response times, and various miscellaneous design flaws. [10][11][12][13] To resolve some of these adverse issues, Sullivan and McDonald 14 developed a robust and inexpensive custom-built sensor, capable of measuring high heat loads in wildland fire scenarios for extended periods of time, without the use of external cooling.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] However, these alternative devices were not without fault, and it was identified that there were various issues such as inconsistencies in the heat flux estimates, slow response times, and various miscellaneous design flaws. [10][11][12][13] To resolve some of these adverse issues, Sullivan and McDonald 14 developed a robust and inexpensive custom-built sensor, capable of measuring high heat loads in wildland fire scenarios for extended periods of time, without the use of external cooling. The sensor estimated the total heat flux emitted from burning vegetative fuels to within one standard deviation of the values measured by a commercial Schmidt-Boelter heat flux gauge and within a comparable response time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The directional flame thermometers (DFT) can be used to measure heat flux. 1 DFTs essentially consist of two parallel Inconel plates separated by ceramic fiber insulation. Temperature is measured at the interior surface of the two plates.…”
Section: Introductionmentioning
confidence: 99%
“…‡ These sensors are not normally intended for use in situations where convection is significant [4,5]. Other gauges that have been developed for research applications, such as the directional flame thermometer (DFT) [6] and the hemispherical heat flux gauge (HFG) [7], have been tested mostly in radiative applications and have not yet been characterized extensively in mixed radiative-convective conditions. The purpose of this paper is to provide a systematic comparison of the responses of four different heat flux gauges in a variety of radiative and mixed radiative-convective environments.…”
Section: Introductionmentioning
confidence: 99%